Legal Certainty of Follow-up Actions on Peace Agreements Resulting from Mediation at the Gorontalo City Consumer Dispute Resolution Agency - Abdul Madjid Podungge; Dwi Indah Yuliani Solihin; Robby Huwana (IHSA Institute, 2025)
The 2024 empirical investigation into the legal certainty of mediation agreements at the Gorontalo City Consumer Dispute Resolution Agency (BPSK) where 27 of 40 cases were successfully resolved underscores the agency’s vital role as an efficient, socio-economic safeguard for vulnerable consumers. However, this study reveals a critical structural vulnerability: unlike the robust enforcement provided for arbitration and court-annexed mediation, the lack of automatic judicial homologation renders BPSK’s Peace Deeds vulnerable, coupled with the recurring problem of business actor non-compliance. These factors position the agreement as a mere moral obligation rather than an enforceable executory title. To transform these outcomes into legally binding instruments, this study advocates for the immediate adoption of an integrated governance model centered on three priority policies: digital integration with the Court's SIPP to streamline ratification and reduce bureaucratic latency; standardization of SOPs and document formats to ensure technical compliance with Article 130 HIR; and mandatory mediator certification to guarantee the drafting of judicially executable agreements. Furthermore, acknowledging the single-jurisdiction scope, future research is necessitated to validate the model's scalability through longitudinal comparative studies across high-volume regions and sector-specific analyses (e.g., digital economy) to ensure efficacy against complex cross-border defaults